1D 1H NMR as a Tool for Fecal Metabolomics. Issue 3 (17th August 2020) - Ganobis, Caroline M.; Al‐Abdul‐Wahid, M. Sameer; Renwick, Simone; Yen, Sandi; Carriero, Charley; Aucoin, Marc G.; Allen‐Vercoe, Emma
Abstract: Metabolomic studies allow a deeper understanding of the processes of a given ecological community than nucleic acid–based surveys alone. In the case of the gut microbiota, a metabolic profile of, for example, a fecal sample provides details about the function and interactions within the distal region of the gastrointestinal tract, and such a profile can be generated in a number of different ways. This unit elaborates on the use of 1D 1 H NMR spectroscopy as a commonly used method to characterize small‐molecule metabolites of the fecal metabonome (meta‐metabolome). We describe a set of protocols for the preparation of fecal water extraction, storage, scanning, measurement of pH, and spectral processing and analysis. We also compare the effects of various sample storage conditions for processed and unprocessed samples to provide a framework for comprehensive analysis of small molecules from stool‐derived samples. © 2020 Wiley Periodicals LLC Basic Protocol 1 : Extracting fecal water from crude fecal samples Alternate Protocol 1 : Extracting fecal water from small crude fecal samples Basic Protocol 2 : Acquiring NMR spectra of metabolite samples Alternate Protocol 2 : Acquiring NMR spectra of metabolite samples using Bruker spectrometer running TopSpin 3.x Alternate Protocol 3 : Acquiring NMR spectra of metabolite samples by semiautomated process Basic Protocol 3 : Measuring sample pH Support Protocol 1 : Cleaning NMR tubes Basic Protocol 4 : Processing raw spectra data Basic Protocol 5 : Profiling spectra Support Protocol 2 : Spectral profiling of sugars and other complex metabolites